Use of the RegCM System over East Asia: Review and Perspectives. (October 2017) - Gao, Xuejie; Giorgi, Filippo
Abstract: The Abdus Salam International Center for Theoretical Physics (ICTP) RegCM system is one of the most commonly used regional climate models (RCMs) over the East Asia region. In this paper, we present a brief review of the RegCM system and its applications to the East Asia region. The model history and plans for future development are described. Previous and ongoing applications, as well as the advantages and biases found in the model system over the East Asia region, are summarized. The model biases that exist are mainly found in the cold seasons, and are characterized by a warm bias at high latitudes and underestimation of precipitation in the south. These biases are similar to those of most global climate models (GCMs). Finally, future plans on the application and development of the model, and specifically on those within the context of the Coordinated Regional Climate Downscaling Experiment (CORDEX), are introduced. This paper is intended to serve as a reference for future users of the RegCM system within the East Asia region.